Kualitas Nutrisi dan Fraksi Serat Wafer Ransum Komplit Subtitusi Dedak Jagung dengan Level Persentase Ampas Sagu yang Berbeda - D. A. Mucra; T. Adelina; A. E. Harahap; I. Mirdhayati; L. Perianita; Halimatussa'diyah Halimatussa'diyah (Jurnal Peternakan, 2020)
Sago waste is the result of agricultural waste whose use as feed is still very limited even though the amount is quite large but sago waste has a high crude fiber content, and low protein content so that is needs further processing, one of which is processing become a wafer complete ration. The study used the Complete Randomized Design (CDR), method with 4 treatments and 4 replications, which consisted of P0: complete wafer ration + 0% sago waste, P1: complete wafer ration + 10% sago waste, P2: complete wafer ration + 20% sago waste, P3: complete wafer ration + 30% sago waste. The  parameters measured were the content of dry matter, crude protein, crude fat, crude fiber, ash content and nitrogen free extract, neutral detergen fiber, acid detergen fiber, acid detergen lignin, cellulosa and hemicellulosa. The result showed that the of the sago waste level to 30% can improve the dry matter, crude fiber, ash content and reduced the nitrogen free extract acid detergen fiber and  acid detergen lignin. The addition of 30%  sago waste level is the best treatment because can decrease neutral detergent fiber 74.09%-57.5%, acid detergent fiber 67.64%-54.23%, dan acid detergent lignin 39.03%-27.17%.